1998
DOI: 10.3354/cr010127
|View full text |Cite
|
Sign up to set email alerts
|

Estimated impacts of soil degradation on the African water balance and climate

Abstract: This study uses a well-established water balance methodology, the Thornthwaite-Mather approach, to evaluate the effects of soil water holding capacity assumptions on estimates of African evapotranspiration rates, moisture deficit, and moisture surplus conditions. Under constant climate conditions, the model tests the impact of using a constant 150 mm soil water holding capacity compared to using a newly derived soil water holding capacity data set (the Dunne-Willmott data set). The study also uses a worldwide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 42 publications
0
21
0
3
Order By: Relevance
“…Land degradation in the African Sahel has also resulted in soil texture change. Feddema (1998) has shown that variations in soil water holding capacity associated with land degradation can have important effects on evapotranspiration and local water balances. The relative contributions of LULC change and soil texture change and the degree to which uncertainty in model response to these change feeds back to the monsoon dynamics is a subject of future study.…”
Section: Discussionmentioning
confidence: 99%
“…Land degradation in the African Sahel has also resulted in soil texture change. Feddema (1998) has shown that variations in soil water holding capacity associated with land degradation can have important effects on evapotranspiration and local water balances. The relative contributions of LULC change and soil texture change and the degree to which uncertainty in model response to these change feeds back to the monsoon dynamics is a subject of future study.…”
Section: Discussionmentioning
confidence: 99%
“…Como consequência dessa degradação, ocorrem alterações em propriedades do solo que controlam os processos fundamentais relacionados com a dinâmica de água, ar e calor (Topp et al, 1994;Feddema, 1998) e crescimento das raízes. Assim, a quantificação dos impactos do manejo sobre a qualidade física do solo deveria ser realizada por meio de atributos que determinam os processos físicos que interferem em aspectos fisiológicos ligados ao crescimento e desenvolvimento das plantas.…”
Section: Introductionunclassified
“…Em geral, a perda da qualidade física do solo está associada com modificações dos arranjos de agregados e poros do solo, reduzindo a disponibilidade de ar, água e nutrientes necessários à produção de biomassa (Six et al, 2004;Omuto, 2008). Essas mudanças interferem nas características da superfície do solo, resultando na compactação do solo (Lanzanova et al, 2007); nas mudanças na distribuição e no tamanho de poros (Dexter, 2004); na diminuição da taxa de infiltração de água no solo (Sobrinho et al, 2003); na diminuição da água disponível (Dexter, 2004); na perda de matéria orgânica (Álvaro-Fuentes et al, 2008); na redução da diversidade e atividade de microrganismos (Six et al, 2004); e no aumento da suscetibilidade à erosão do solo (Feddema, 1998;Lal, 2000;Richard et al, 2001). …”
Section: Introductionunclassified
“…A degradação física é um dos componentes do processo de degradação do solo, geralmente associado às perdas de matéria orgânica e da integridade estrutural dos solos. Como consequência da degradação física, há alterações em propriedades do solo que controlam processos fundamentais relacionados com a dinâmica de água, ar e calor (Feddema, 1998).…”
Section: Introductionunclassified